Self-organisation and empowerment in the struggle against silence. Network of Tortured People of Navarre - Soto Nolasco, Mikel (Torture Journal, 2023)
In 2021, a group of tortured people and their relatives in Navarre started a process of self-organisation that culminated in 2022 with the birth of the organisation Network of Tortured People of Navarre. The process of self-organisation of tortured people in Navarra is an uncommon phenomenon, which can offer interesting lessons especially for torture victims in other countries and contexts. The aim of this article is to describe a survivor-lead experience and to analyse the keys to this process of collective empowerment. The article has two parts: the first explains the phenomenon of torture in Navarre from the 1960s, in Franco's dictatorship, to the present day using data from the Study on Torture in Navarre, highlighting significant cases or events. The second part is focused on describing the self-organising process of the victims and some lessons that we think may be useful for other realities and groups of torture victims who want to generate self-organising processes. The article analyses some aspects in the genesis and the first steps of the Network with emphasis on those aspects that can be useful to other victims' organisations in their struggle against torture. To do so, we will analyse these aspects: The political and social context in which the Network was born, the Network's strategies for dealing with victims' difficulties in working with their "traumatic event", the organisational structure and development of the network, the Network's basic principles and demands, the Network's strategy and philosophy of work, the Network's policy on relations and alliances and the opportunities and consequences of the process being driven by victims of torture.